2022
DOI: 10.1265/ehpm.21-00254
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA2 deficiency in NSCLC: a clinicopathologic and immunohistochemical analysis of a large series from a single institution

Abstract: Background: SMARCA2 (SWI/SNF Related, Matrix Associated, Actin Dependent Regulator of Chromatin, Subfamily A, Member 2) is an important ATPase catalytic subunit in the switch-sucrose nonfermenting (SWI/SNF) complex. However, its relationship with the pathological features of NSCLC and its prognosis remain unclear. Methods: We retrospectively reviewed 2390 patients with surgically resected NSCLC, constructed tissue microarrays (TMAs) and performed immunohistochemical assays. We analyzed the correlation of SAMRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…ARID1A is expressed in non-small cell lung cancer at rates of 1.2% to 7.5% [24][25][26], consistent with our research. Previous studies have found that abnormal ARID1A expression is associated with poor overall survival in patients with ARID1A-mutated non-small cell lung cancer [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…ARID1A is expressed in non-small cell lung cancer at rates of 1.2% to 7.5% [24][25][26], consistent with our research. Previous studies have found that abnormal ARID1A expression is associated with poor overall survival in patients with ARID1A-mutated non-small cell lung cancer [25][26][27].…”
Section: Discussionsupporting
confidence: 91%